Localized corrosion induced by MnS inclusions in U71Mn rail steels - Chao Ji; Liya Guo; Haiyang Wang; Tengshi Liu; Xicheng Wei; Han Dong (Journal of Materials Research and Technology)
To understand the corrosion mechanisms of rail steels, immersion tests were conducted on U71Mn rail steels produced in 1994 and 2021. It was observed that, at the onset of corrosion, only matrix near clustered MnS inclusions dissolved. Further characterization revealed that this was due to the combined effects of lower Volta potential, higher lattice distortion of the surrounding matrix, and strip-shaped carbides in the surrounding matrix induced by the clustered distribution of MnS. Consequently, the U71Mn2021 rail steel, with fewer MnS clusters formed, exhibited better corrosion resistance, as evidenced with electrochemical measurements. These findings suggest that refined processing techniques to control inclusion formation could be effective methods for developing U71Mn rail steels with greater corrosion resistance.